The Relationship between Business Performance and HRV Biofeedback Profiles among Small Entrepreneurs - Nazrolnizah, Mohamad Noorzeli; Muhammad Nubli, Abdul Wahab (Center for Promoting Ideas (CPI), USA., 2017)
Self-performance is important among entrepreneurs due to increasing the business enhancement. Recent research has explored how business performance is influenced by different factors. HRV (Heart Rate Variability) Biofeedback, for instance, is a phenomenon where physiological changes occur in the interval between heartbeats. This study therefore examined the relationship between HRV Biofeedback training, increasing business performance and success in business. Nevertheless, previous literature showed that there is less current study which focused on the self-performance using Biofeedback techniques among entrepreneurs in Malaysia. Thus, this study was aimed to: 1) Identify the profile of Heart Rate Variability (HRV) among small entrepreneurs and 2) Examined the measure of success among small entrepreneurs through increased income earnings after the HRV training. A total of 50 respondents of small entrepreneurs were recruited in this study. The data collected involved a questionnaire survey with participants, profit and sales analysis and analysis of HRV. Statistical correlation analysis was used to examine the relationship between business performance and business insights from the point of HRV. The finding shows that there is a very strong relationship between performance increasing in term of incomes with the profile of HRV among participants with the score of 0.984. This showed that HRV Biofeedback training technique is appropriate to be used as an intervention program to increase entrepreneurship skills among small entrepreneurs in Malaysia.